2020
DOI: 10.5812/amh.100630
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Effects of Propolis Against Leishmania major In Vitro and In Vivo

Abstract: Background: Propolis is produced by honey bees from plants, buds, and exudates and as an antiseptic is used to treat several diseases, such as acne and wounds. Objectives: Due to some difficulty in the treatment of cutaneous leishmaniasis, the aim of this study was to evaluate the propolis extract function against Leishmania major.Methods: Different concentrations (9.375, 18.75, 37.5, 75, 150, and 300 µg/mL) of both Ethanolic Extract of Propolis (EEP) and the standard drug (Glucantime) were prepared for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Tavakoli et al observed that the ethanolic extract of Iranian propolis inhibited the growth of promastigote forms of L. major, as well as the standard drug Glucantime (meglumine antimoniate) at concentrations >37.5 µg/mL in vitro (p > 0.05). More importantly, in a mouse model of cutaneous leishmaniasis (L. major), treatment with 4% ethanolic propolis extract (4 g extract plus 96 g vaseline-oserin) reduced the size of skin lesions with similar efficacy as Glucantime, the standard antileishmanial treatment in much of the world [138].…”
Section: Propolis In Animal Models Of Leishmaniasismentioning
confidence: 99%
“…Tavakoli et al observed that the ethanolic extract of Iranian propolis inhibited the growth of promastigote forms of L. major, as well as the standard drug Glucantime (meglumine antimoniate) at concentrations >37.5 µg/mL in vitro (p > 0.05). More importantly, in a mouse model of cutaneous leishmaniasis (L. major), treatment with 4% ethanolic propolis extract (4 g extract plus 96 g vaseline-oserin) reduced the size of skin lesions with similar efficacy as Glucantime, the standard antileishmanial treatment in much of the world [138].…”
Section: Propolis In Animal Models Of Leishmaniasismentioning
confidence: 99%
“…It causes clinical signs from cutaneous form to the visceral form, fever, splenomegaly (enlargement of the spleen, manifested in the great majority of patients), hepatomegaly (enlargement of liver), pallor (caused by severe anemia), leucopenia (low white blood cell count), and weight loss (Gervazoni et al, 2020). Leishmania has two stages in its life cycle, including promastigote, and amastigote (Tavakoli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%